2023
DOI: 10.3389/fcvm.2023.1113886
|View full text |Cite
|
Sign up to set email alerts
|

Single coronary artery presenting dilated cardiomyopathy and hyperlipidemia with the SCN5A and APOA5 gene mutation: A case report and review of the literature

Abstract: We present a 55-year-old man with chest tightness and dyspnoea after activity lasting for 2 months who was diagnosed with single coronary artery (SCA) and presented with dilated cardiomyopathy (DCM) with the c.1858C > T mutation in the SCN5A gene. The computed tomography coronary angiogram (CTCA) showed congenital absence of the right coronary artery (RCA), and the right heart was nourished by the left coronary artery branch with no apparent stenosis. Transthoracic echocardiography (TTE) revealed enlarg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Recently, genome-wide association studies (GWASs) confirmed the strong association between single-nucleotide polymorphisms and some electric, structural and functional phenotypes of the cardiovascular system [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genome-wide association studies (GWASs) confirmed the strong association between single-nucleotide polymorphisms and some electric, structural and functional phenotypes of the cardiovascular system [29,30].…”
Section: Discussionmentioning
confidence: 99%